2020
DOI: 10.1007/s00787-020-01479-7
|View full text |Cite
|
Sign up to set email alerts
|

Negative and disorganized symptoms mediate the relationship between verbal learning and global functioning in adolescents with early-onset psychosis

Abstract: Neurocognitive deficits are associated with impaired global functioning and psychotic symptoms. However, whether symptoms can mediate the relationship between neurocognition and global functioning in adolescent psychosis is unclear. Here, we investigated if symptoms assessed with the Positive And Negative Syndrome Scale (PANSS), mediated the relationship between neurocognitive performance and global functioning in adolescents with non-affective early-onset psychotic disorders (EOP). Sixty-one adolescent EOP pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 77 publications
2
9
0
Order By: Relevance
“…These findings illustrate a crucial need for increased knowledge of pathological mechanisms associated with EOP. In a previous study from our group including an overlapping EOP sample with the present study, negative and disorganized symptoms were found to mediate the relationship between verbal learning and global functioning (37). However, to the best of our knowledge, the factorial structure of negative symptoms and how specific subdomains of negative symptoms relate with cognition, have not yet been investigated in adolescent patients with EOP.…”
Section: Introductionmentioning
confidence: 43%
“…These findings illustrate a crucial need for increased knowledge of pathological mechanisms associated with EOP. In a previous study from our group including an overlapping EOP sample with the present study, negative and disorganized symptoms were found to mediate the relationship between verbal learning and global functioning (37). However, to the best of our knowledge, the factorial structure of negative symptoms and how specific subdomains of negative symptoms relate with cognition, have not yet been investigated in adolescent patients with EOP.…”
Section: Introductionmentioning
confidence: 43%
“…The patients were recruited from 2005–2007 (Early-Onset Study) and 2013–2018 (Youth-TOP). Cognitive data from the two cohorts have previously been published (Holmen et al, 2010; Juuhl-Langseth et al, 2014; Smelror et al, 2020). The majority of patients in both cohorts were recruited from adolescent psychiatric inpatient units and outpatient clinics in the Oslo region.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired verbal learning in CHR is also one of the strongest cognitive predictors for psychosis development (Carrio ´n et al, 2018;Fusar-Poli et al, 2012;Seidman et al, 2016). In adolescent EOP, specific associations have been reported between verbal learning, negative and disorganized symptoms, and functional outcome (Smelror et al, 2020). Thus, increased knowledge of how cognitive performance in EOP develops after the onset of illness can inform us about psychosis etiology and be beneficial in the development of cognitive remediation strategies, treatment planning and rehabilitation programs, focusing on improving functional outcome in adolescents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During adolescence, emerging psychotic and personality disorders, including schizophrenia, bipolar disorder and borderline personality disorder, are major differential diagnoses next to mood and anxiety disorders [5][6][7][8][9][10][11][12]. Recent and very important research has sharpened the understanding of these conditions [13,14], which differentiates them from normal development including puberty. Many of these conditions have their onset in adolescence rather than in adulthood, including subclinical precursors as a prodromal state.…”
mentioning
confidence: 99%